Roll Motion Analysis on Unmanned Surface Vehicle with Remote Controlled Weapon Station Models to Combat Piracy in Surabaya West Access Channel - Habibah, Natasya; Habib, Kevin Rizqul; Claresta, Gianiti; Siregar, Hadi Mulki (Department of Naval Architecture - Diponegoro University, 2021)
The dense shipping activity in the Surabaya West Access Channel (SWAC) is accompanied by a high rate of piracy which had 13 cases during 2013–2018. An Unmanned Surface Vehicle (USV) with Remote Controlled Weapon Station (RCWS) was created to overcome this piracy, increase work effectiveness, and reduce potential casualties. This study aims to create a design of USV equipped with RCWS complies with the requirements then analyzes the stability and seakeeping (roll motion) because it is one of the most determining factors of the stability and safety of the ship. The research method in this study is a simulation process based on system engineering theory starting from the formulation of requirements, design making, and then simulation. Five design models are created and simulated to analyze their stability and seakeeping performance. The design results are a monohull USV equipped with an RCWS with the main dimension of 1.7 m long, 0.9 m wide, and 1.04 m high. The stability simulations conclude that Model 4 is the most stable platform with the highest peak value of GZ for 0.112 m in angle degree of 108.2°. The seakeeping simulations show that at wave heading 45°, model 3 has the highest RAO with the peak value of 4.703 at the frequency of 0.4 rad/s. At wave heading 90°, model 5 has the highest RAO with the peak value of 0.095 at the frequency of 0.4 rad/s. At wave heading 135°, model 1 has the highest RAO of 0.012 at the frequency of 0.581 rad/s.